Effect of the M3+ cation size on the structural and high temperature phase transitions in Sr2 MSbO6 (M = Ln, Y) double perovskites. (17th February 2017) - Orayech, B.; Faik, A.; Igartua, J.M.
Graphical abstract: We present a rigorous study of the crystal structures at room temperature of Sr2 MSbO6 (M= Ln and Y) compounds by using Synchrotron and laboratory XRPD. An in situ high-temperature measurements show the existence of two temperature driven phase-transitions: a discontinuous one, from the RT symmetry P 2 1 / n to R 3 ¯ and a continuous one from the latter symmetry to the highest one, the cubic Fm 3 ¯ m . The physics behind the origin of the phase-transition sequence observed in the antimony materials is discussed. The phase transition temperatures are correlated to the M 3+ cation size. The analysis of the phase transitions and the structural refinements was done using a novel tool: the symmetry-adapted modes instead of the conventional atomic coordinate method. A step forward in these analysis consisting of parametrization of the refinements by fixing a selected common direction in the sub-space spanned by X 5 +, this parametrization is confirmed by energy calculations (to be published) that has given us more physical arguments that corroborate the main conclusions of the workflow we are developing. Abstract: In the present work, synchrotron X-ray powder-diffraction measurements at room temperature and laboratory X-ray powder-diffraction measurements at high temperatures of nine members of the antimony family Sr2 MSbO6 M = Ln (Nd, Eu, Gd, Dy, Ho, Er, Tm, Yb) and Y ; are reported. Six of them are synthesized for the first time in this work. The crystal structures at room temperature of these compounds are determined and their symmetries are described in the P 2 1 / n ( a - a - b + ) space group (No. 14, non-standard setting). The materials have double perovskite structure with 1:1 ordered arrangement of the B sites. The high-temperature measurements show the existence of two temperature driven phase-transitions: a discontinuous one, from the RT symmetry to R 3 ¯ ( a - a - a - ) and a continuous one from the latter symmetry to the highest one, the cubic Fm 3 ¯ m ( a 0 a 0 a 0 ). The phase transition temperatures are correlated to the M 3+ cation size. The analysis of the phase transitions and the structural refinements have done using the symmetry-adapted modes. A step forward in these analysis is performed: parametrization of the refinements by fixing a selected common direction in the sub-space spanned by X 5 +, tri-linearly coupled to the order parameters of the cubic to monoclinic first order phase transition.